Optimization of a novel series of potent and orally bioavailable GPR119 agonists. Issue 15 (1st August 2017) - Koshizawa, Tomoaki; Morimoto, Toshiharu; Watanabe, Gen; Watanabe, Toshiaki; Yamasaki, Nao; Sawada, Yoshikazu; Fukuda, Tomoaki; Okuda, Ayumu; Shibuya, Kimiyuki; Ohgiya, Tadaaki
Graphical abstract: Abstract: We describe the discovery and optimization of a novel series of furo[3, 2- d ]pyrimidines as G protein-coupled receptor 119 agonists. Agonistic activity of4 (EC50 = 129 nM) was improved by replacing the intramolecular hydrogen bond between the fluorine atom and the aniline hydrogen in the head moiety with a covalent C-C bond to enhance conformational restriction, which consequently gave a lead compound12 (EC50 = 53 nM). Optimized compound26, which was identified by the further optimization of12, exhibited potent activity (EC50 = 42 nM) with improved clearance in liver microsomes and induced a 33% reduction in blood glucose area under the curve at a dose of 10 mg/kg in an oral glucose tolerance test in C57BL/6N mice.